ANALISIS TINGKAT PENGETAHUAN MASYARAKAT DALAM PENGGUNAAN QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS) SEBAGAI SISTEM PEMBAYARAN DIGITAL (Studi Kasus Masyarakat Nagari Matur Mudiak) - Sefhiyola Abelsa; Awaluddin (STKIP Subang, 2026)
Several small businesses in Nagari Matur Mudiak have begun to accept QRIS as a means of payment, triggering this research because it shows the awareness and utilization of the system by the community. The purpose of the research was to measure the extent to which residents know and use the Quick Response Indonesia Standard (QRIS) as a digital payment method. The approach used was descriptive qualitative with primary and secondary data, collected through observation, interviews, and documentation. Analysis of data from interviews and field notes showed that although QRIS was known in a basic way, in-depth understanding of how it works was still limited. Several respondents praised the ease and security features of QRIS, but complained about the lack of information and resources. Technical constraints such as unstable internet connections indicated the need to improve local IT infrastructure. Some respondents understood QRIS-based digital payment applications and mentioned additional benefits such as discounts and rebates that attracted users. Research recommendations include education, information campaigns, and direct training to increase awareness and knowledge of the Nagari Matur Mudiak community about QRIS.